Combined phase I/II study of imexon (AOP99.0001) for treatment of relapsed or refractory multiple myeloma - Möhler, Thomas; Feneberg, Reinhard; Ho, Anthony Dick; Golenkov, Anatoly K.; Ludwig, Heinz; Kropff, Martin; Khuageva, Nuriet K.; Hajda, Jacek; Broen, Ingo von; Goldschmidt, Hartmut (Anti-cancer drugs, 2010)
Imexon [AOP99.0001 (4-imino-1,3-diazobicyclo[3. 1. 0]-hexan-2-one)] belongs to a novel class of promising anticancer agents that induce tumor apoptosis through oxidative stress. Clinical experience since the late 1960s has provided initial evidence for a clinical antitumor activity. Our open-label, multicenter phase I clinical trial was designed to further investigate the adverse event (AEs) profile and pharmacokinetics of AOP99.0001 in pretreated myeloma patients and collect initial data on the potential clinical efficacy in this indication. Thirty-six patients with relapsed or refractory myeloma, who had been pretreated with at least two lines of therapy earlier, were included. Imexon was applied intravenously on 5 consecutive days for 2 weeks (d1-5 and d8-12) for a 3-week cycle. The plasma half-life of AOP99.0001 and its active metabolite AOP99.0002 was found to be approximately 1.2 and 2.6 h, respectively. The mean duration of treatment with Imexon was 6.8 weeks in a dose range between 50 and 1000 mg/m2 without reaching dose-limiting toxicity. Drug-related AEs occurring with a frequency of greater than 10% were fatigue, nausea, constipation, headache, asthenia, anemia, thrombocytopenia, leukopenia and creatinine increase. A total of nine severe adverse events occurred in three patients. No mortality was encountered when patients were on treatment with Imexon. Preliminary antimyeloma efficacy of AOP99.0001 was observed with 1 minimal response, 12 (36%) stable disease responses, and all other evaluable patients had progressive disease. Remarkably, the patient with minimal response also experienced a complete clinical resolution of myeloma-associated polyneuropathy. Overall, Imexon was safe and well tolerated in the dose range investigated. Imexon showed minor clinical activity as a single agent in heavily pretreated myeloma patients. On account of its unique mechanism of action, favorable toxicity profile, initial clinical evidence for antimyeloma activity, and its known synergistic activity in combination with approved agents for myeloma treatment, AOP99.0001 is recommended for future clinical studies in combination regimens in multiple myeloma.